COMMUNICATIVE GAMES: ENHANCING STUDENTS’ SPEAKING SKILLS AT UNISKA CAMP - Avinta Ika Nurrahma; Ervina Damayanti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This study aims to enhance the students’ speaking skills of first-semester students at Uniska Camp. The method used was classroom action research with 150 participants. The procedures used were planning, acting, observing, and reflecting. It was done into two cycles in each cycle consisted of three meetings. The researcher used collaborative action research with some of the English teachers. The data were collected through classroom observation, interviews, and tests. The quantitative data were obtained from tests, and the qualitative data were collected through classroom observation, interviews, and documentation. Descriptive statistics analyzed the quantitative data, and qualitative data were analyzed by data display, verifying, and drawing a conclusion. This study's findings indicate that communicative games can improve students' speaking skills. Therefore, the criteria of success had been determined. It is crucial to note that communicative games have contributed a positive impact on teaching learning process. This also implies the communicative games expected to enhance students’ enthusiasm and motivation. Clearly, It gives positive improvement on students’ active participation, confidence and their fluency in speaking skill. In short, it can be described that the strategy of teaching and learning creates good, enjoyable circumstances and reduces the boredom and stress of learning process.